Proceedings of the 2022 7th International Conference on Modern Management and Education Technology (MMET 2022) 2022
DOI: 10.2991/978-2-494069-51-0_37
|View full text |Cite
|
Sign up to set email alerts
|

Exploration and Practice of Virtual Simulation Experiment Teaching in the Cultivation of Ship Painting Talents

Abstract: With the rapid development of higher education in the new era, virtual simulation technology has been continuously integrated into various education and teaching. This paper briefly analyzes the application of the new experimental teaching mode of "Internet + experimental teaching" constructed by virtual experimental project design, network technology, multimedia technology and humancomputer interaction technology in the training of marine talents. The combination of virtual simulation teaching and practical o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…Their results demonstrated that the platform could successfully meet the real-time requirements of virtual robot simulation movement [6]. Zhang et al [7] and Lu et al [8] established VSEPs for the teaching and practice of oceanography and hydraulic fracturing, respectively. Moreover, Liu et al designed an interactive simulation-experimental teaching system of virtual shipyard and marine, providing an experimental platform that integrates learning, experiencing and testing together [9].…”
Section: Introductionmentioning
confidence: 99%
“…Their results demonstrated that the platform could successfully meet the real-time requirements of virtual robot simulation movement [6]. Zhang et al [7] and Lu et al [8] established VSEPs for the teaching and practice of oceanography and hydraulic fracturing, respectively. Moreover, Liu et al designed an interactive simulation-experimental teaching system of virtual shipyard and marine, providing an experimental platform that integrates learning, experiencing and testing together [9].…”
Section: Introductionmentioning
confidence: 99%
“…There are strict requirements for the technical level of the operators; otherwise, it is easy to cause problems such as increased costs, decreased spraying quality [2], and lower productivity [3]. Currently, physical hands-on training [4], virtual simulation training [5], and video teaching are usually used to improve the technical level of sprayers, but these methods suffer from environmental pollution, high costs, and weak human-computer interaction. Therefore, finding a green and efficient spraying training program is an urgent problem.…”
Section: Introductionmentioning
confidence: 99%